Logistical challenges of fourth generation ports diagnosis and modernization in emerging countries - Boyano-Fram, Teófilo Omar (EFIM Ediciones, 2019)
Just as the Information Systems and the ships or vessels are being perfected and facilitating the attention to the users, it is of no use if the Port as a whole is not prepared to meet the demands of the Market. The following text is the result of a review of the literature related to the subject, which describes the Referents related to Ports of Fourth Generation, also includes the challenges that will have to face in a country that fails to have development indices. Economic, in which it is inferred that public policies aimed at strengthening the Port at the level of the most developed will be the way to enter Fourth Generation Ports.